THE EFFECT OF TEACHING CRITICAL THINKING SKILL THROUGH PROBLEM SOLVING TECHNIQUE TOWARD STUDENTS’ WRITING SKILL IN STKIP ADZKIA PADANG - Rona Rossa (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract : The Effect Of Teaching Critical Thinking Skill Through Problem Solving Technique Toward Students’ Writing Skill In Stkip Adzkia Padang. This research was aimed to find out the effect of teaching Critical Thinking Skill through Problem Solving technique toward students’ writing skill of Analytical Exposition text in STKIP Adzkia Padang. This research was a quasi-experimental research. It was conducted at STKIP Adzkia Padang. The population of this research was the students at fifth semester of PGSD which consisted of three classes in academic year 2014/2015 who was totally ninety two students. The instrument that was used for this research was writing. T-test analysis was used in analyzing the data. The result of this research revealed that: the students who were taught by Critical thinking Skill through Problem Solving Technique were better than students who were taught by brainstorming technique toward students’ writing skill. Based on findings, it was be concluded that Critical Thinking skill through Problem Solving technique gave significant effect on students’ writing skill.  Keywords : Critical Thinking Skill through Problem Solving Technique,                    Writing Skill